A Conceptual Curriculum Design Approach for Educating Engineers of and for the Future - Satesh Namasivayam; Abdulkareem Sh. Mahdi Al-Obaidi; Mohammad Hosseini Fouladi (Indonesian Journal of Science and Technology, 2023)
The 4th Industrial Revolution (I4) highlights the demand for engineers equipped with technical expertise, emotional intelligence, communication, leadership, and critical thinking skills to navigate the complexities of modern engineering. This conceptual paper presents a future-oriented approach to engineering curriculum development, emphasizing the adoption of Outcome-Based Education (OBE) and project-based learning. The integration of key frameworks, such as the Conceive Design Implement Operate (CDIO) model and blended learning techniques, enhance the learning experience. The curriculum aims to align with global goals, including the UN Sustainable Development Goals and the 14 Grand Challenges for Engineering. An innovative curriculum is designed to inspire students' passion for engineering and engage them with emerging technologies, such as additive manufacturing and artificial intelligence. By equipping graduates with the necessary skills and knowledge, this curriculum strives to make a significant impact on society, fostering sustainability and addressing complex engineering challenges. This paper contributes to the field of engineering education by providing a comprehensive and forward-thinking approach to curriculum development.